2005
DOI: 10.1002/cne.20618
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide-containing pathways in the rat forebrain

Abstract: The present study focuses on the topographical distribution of calcitonin gene-related peptide (CGRP)-containing cell bodies and fibers and their connections and pathways in the rat forebrain. We confirm previously reported CGRP projections from the perifornical area of the hypothalamus to the lateral septum, from the posterior thalamus to the caudate putamen and cerebral cortex, and from the parabrachial nuclei to the central extended amygdala, lateral hypothalamus, and ventromedial thalamus. Despite previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 89 publications
5
91
1
Order By: Relevance
“…Last, intra-BNST infusions of calcitonin gene-related peptide (CGRP) was reported to enhance startle and increase Fos expression in CeA (Sink et al 2011). However, a patch-clamp study found that CGRP potentiates GABAergic inhibition in neurons of BNST-AL (Gungor and Pare 2012), the BNST region receiving CGRP inputs from the parabrachial nucleus (Gustafson and Greengard 1990;Dobolyi et al 2005). Since most BNST neurons are GABAergic (Esclapez et al 1993;Poulin et al 2009), these results suggest the startle enhancement produced by intra-BNST infusions of CGRP is due to the inhibition of BNST-AL neurons and consequent disinhibition of CeA.…”
Section: Prior Lesion and Inactivation Studies On The Role Of Bnst Inmentioning
confidence: 70%
“…Last, intra-BNST infusions of calcitonin gene-related peptide (CGRP) was reported to enhance startle and increase Fos expression in CeA (Sink et al 2011). However, a patch-clamp study found that CGRP potentiates GABAergic inhibition in neurons of BNST-AL (Gungor and Pare 2012), the BNST region receiving CGRP inputs from the parabrachial nucleus (Gustafson and Greengard 1990;Dobolyi et al 2005). Since most BNST neurons are GABAergic (Esclapez et al 1993;Poulin et al 2009), these results suggest the startle enhancement produced by intra-BNST infusions of CGRP is due to the inhibition of BNST-AL neurons and consequent disinhibition of CeA.…”
Section: Prior Lesion and Inactivation Studies On The Role Of Bnst Inmentioning
confidence: 70%
“…This antiserum was raised in goat against synthetic rat Tyr-CGRP (23-27) ␥-globulin and is specific for the whole molecule (1-37) and 23-37 fragment. This antibody reacts with rat CGRP but does not cross-react (<0.01%) with calcitonin, somatostatin, or amylin 8 -37 (dot blot); specific reactivity is eliminated by preincubation of the antiserum with 10 M rat CGRP (manufacturer's technical information), and fluorescence immunostaining of terminals in rat forebrain is eliminated by preincubation (2 days, room temperature) with 5 M rat CGRP (Dobolyi et al, 2005). This antibody produces a similar pattern of immunoreactivity in the rodent dorsal horn as demonstrated in numerous previous publications (e.g., Alvarez et al, 2004).…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…CGRP, a 37-amino acid neuropeptide, is produced by the alternative splicing of the calcitonin gene (8). It is widely distributed in the central and peripheral nervous systems (9) and has been considered to possess diverse functions (10).…”
mentioning
confidence: 99%